Selection of Water Treatment Technology in the Mineral Water Industry Using the Vikor Method - Dyah Anggraini; Tri Widjaya (Publikasi Indonesia, 2025)
The bottled water industry applies different water treatment technologies, with some industries using technologies that are less appropriate when considering the type of raw water to be processed. Effective water treatment is the key to success in the bottled water industry, as product quality and business processes heavily depend on the selected water treatment technology. This study aims to evaluate and select the optimal water treatment technology for the bottled water industry using the Vise Kriterijumska Optimizacija Kompromisno Resenje (VIKOR) method, along with economic evaluation through metrics such as IRR, NPV, and PBP. This method considers various relevant criteria, such as product quality, efficiency, costs, environmental impact, and customer satisfaction. The research process begins with data collection from several water treatment technologies used in the bottled water industry in the Pandaan District, Pasuruan Regency, East Java Province. The VIKOR method is then applied to analyze and compare these technologies, along with economic evaluation using metrics such as IRR, NPV, and PBP. The results of the study indicate that the technology used by Company F ranked highest with the lowest compromise value (Q). The findings of this study are expected to provide insights for the bottled water industry in selecting the appropriate water treatment technology, as well as contribute to research in the field of water treatment. Recommendations for the implementation of the selected technology are also presented to improve efficiency and product quality.